"A Masterpiece or Nothing": Balzacian and Jamesian Elements in Jacques Rivette's La Belle Noiseuse. Issue 2 (1st April 2022) - CARBALLO, PABLO ZAMBRANO
Abstract : The complexity of Jacques Rivette's La Belle Noiseuse (1991) rests largely on a rich intertextual framework in which both Balzac's Le Chef-d'œuvre inconnu and Henry James's Notebooks and several of his short stories play a key role. Besides a series of evident plot elements drawn from Balzac's story, the pictorial and artistic theory discussed in the film shows significant links with Frenhofer's well-known speeches about art and painting, as well as with the conviction that what really distinguishes art is the creation process and not its final result. On the other hand, the reasons why Rivette approached James's work have much to do with his priest-like reverence for literature and art, his reflection on the deep joys and sorrows of the creative process and his taste for the projection of those intimate reflections in short stories such as "The Madonna of the Future", "The Liar" and "The Figure in the Carpet". By bringing Balzac and James together, Rivette proves the complementarity of two authors who focused their powerful gaze on the mystery of artistic creation, a key topic in La Belle Noiseuse .